SEX ROLE ORIENTATION AND CAREER SPECIALIZATION AMONG FEMALES ON MANAGERIAL POSITIONS IN NIGERIA - Ndom R; Mowaiye Fagbemi, o (Getsempena Health Science Journal, 2025)
Sex role attributes and orientation are influenced by societal socialization and tendencies and individuals pick cues related to such as they may with varied intervening variables. Such variables could be level of education, parental background , peer influences , school type influences amongst others. In almost every society sex role attributes is a determinant of many things for individuals and societies. Career choice for many may not be an easy choice to make especially for individuals who may be stereo-typical gender wise . It thus seem probable that there could be influences on gender beliefs and career choices especially where some careers are perceived as masculine and majorly for males or feminine and mainly for females. The present study sought to find out if females holding high positions of authority could be said to be stereotypical or otherwise as regards sex and gender role orientation and how that relates or not to career choice and area of specialization